Strengthening Mechanisms of Magnesium-Lithium Based Alloys and Composites - C. O. Muga; Z. W. Zhang (Advances in Materials Science and Engineering)
Mg-Li based alloys are widely applied in various engineering applications. The strength of these alloys is modified and enhanced by different strengthening mechanisms. The strengthening mechanisms of these alloys and their composites have been extensively studied during the past decades. Important mechanisms applied to strengthening the alloys include precipitation strengthening, solution strengthening, grain and subgrain strengthening, and dislocation density strengthening. Precipitation and solution strengthening mechanisms are strongly dependent on composition of the alloys and thermal treatment processes, whereas grain and subgrain and dislocation density strengthening mechanisms majorly depend on thermomechanical processing. In this paper, recent studies on conventional processes for the strengthening of Mg-Li based alloys are summarized as they are critical during the alloys design and processing. Main strengthening mechanisms are objectively reviewed, focusing on their advantages and drawbacks. These can contribute to enhancing, initiating, and improving future researches for alloys design and suitable processing selection.